Turbine heat transfer and aerodynamic measurements and predictions for A 1.5 Stage configuration - Chana, K; Singh, UK; Povey, T (2004)
This paper considers the surface heat transfer rate to, and aerodynamics of, a 1.5 stage turbine - a high pressure (HP) turbine stage followed by an intermediate pressure (IP) vane. Unsteady interactions arising from the relative motions of vane/blade rows are examined. The IP vane was of structural type, and was designed with a vane count of 26. Measurements of time-mean heat transfer and aerodynamics are seldom performed in 1.5 stage turbines, because of the necessary complexity of the experimental setup required for such investigations. This paper presents both steady and unsteady measurements conducted in an engine-size research turbine, operated at engine-representative non-dimensional conditions. Measurements are compared to the predictions from a three-dimensional, viscous, non-linear, time accurate flow solver. An unstructured grid was used, and, by using the Erdos direct storage technique, the code was extended to allow for non-integer vane/blade pitch ratios. A prediction was performed in which all three vane/blade rows were simultaneously modelled. The measured and predicted unsteady surface heat transfer rates for the IP vane and HP rotor blade were in good agreement, and demonstrated that the interactive effects arising from the relative motion of these components were significant.